Fishing boats - Albert Walton DeRome:::Creator::::::::::::
A lampara at dock, with felucca and purse seiners in the background, at Harbor Wharf number 2, Fisherman's Wharf, near Booth's Cannery in Monterey, California. The photographer, Albert Walton DeRome (Al Aagard), was a cousin of Carol Henning Steinbeck. (see Steinbeck Studies 15.1 (2004): 18.)